The Imagined Ladyland in Rokeya Sakhawat Hossain’s Sultana’s Dream - Khatun, Mst. Rokeya; Ahammed, A. K. Zunayet (Muslim English Literature, 2024)
This study investigates the imagined Ladyland in Sultana's Dream to show Rokeya Sakhawat Hossain’s vision of women’s empowerment and emancipation. The Ladyland epitomizes the triumph of the scientific, righteous, progressive and benevolent ingenuity in women. It also serves as a symbol of women empowerment, and a critique of colonialism and patriarchy. In the Ladyland, there is no patriarchy, and only matriarchy prevails. While women avail all the rights, needs, and privileges, the women living in Rokeya’s society are deprived of all these. They are confined to the domestic domain whereas men work outdoors. Therefore, to take women out of their shells, the writer emphasizes the necessity of empowering women through modern education and social reform. This article employs a qualitative descriptive method to provide a detailed textual analysis of the Ladyland and the Feminist Literary Theory to analyze the portrayal of the Ladyland which advocates for the emancipation of women of colonial East Bengal and beyond from the clutches of patriarchy and other traditional constraints through their empowerment, to build up a more equitable society. This study continues to make a significant contribution to world literature, offering future researchers valuable insights, ideas, and viewpoints on the writer and her works.